Effectiveness and Safety of Anti-CD19 Chimeric Antigen Receptor-T Cell Immunotherapy in Patients With Relapsed/Refractory Large B-Cell Lymphoma: A Systematic Review and Meta-Analysis - Ying, Zhitao; Song, Yuqin; Zhu, Jun (Frontiers in Pharmacology, 2022)
Aim: To investigate the effectiveness and safety of using chimeric antigen receptor (CAR) T cell therapies targeting CD19 in patients with diffuse large B-cell lymphoma (DLBCL). Methods: PubMed, Embase, and the Cochrane Library were searched for reports published from database inception up to July 2021. The present meta-analysis included clinical response outcomes, survival outcomes, and safety analyses. For qualitative analysis that could not be combined, the data were presented in a tabular form. Subgroup analyses were also performed according to the costimulatory domains, generic names, and study designs. Results: Twenty-seven studies (1,687 patients) were included. The pooled 12-months overall survival (OS) rate was 63% (95%CI: 56–70%). The pooled best overall response (BOR) was 74.0% (95%CI: 67–79%), with a best complete response (BCR) of 48% (95%CI: 42–54%) and a 3-months CR rate (CRR) of 41% (95%CI: 35–47%). The subgroup analyses by costimulatory domain suggested statistically significant differences in BOR and BCR, whereas not in the 12-months OS rate and 3-months CRR. Among the patients evaluable for safety, 78% (95%CI: 68–87%), 6% (95%CI: 3–10%), 41% (95%CI: 31–52%), and 16% (95%CI: 10–24%) experienced cytokine release syndrome (CRS), severe CRS, neurotoxicity, and severe neurotoxicity, respectively. Compared with the CD28 costimulatory domain, the 4-1BB-based products showed a better safety profile on any-grade CRS (p < 0.01), severe CRS (p = 0.04), any-grade neurotoxicity (p < 0.01), and severe neurotoxicity (p < 0.01). Conclusion: Anti-CD19 CAR-T cell immunotherapy has promising effectiveness and tolerable severe AE profile in DLBCL patients. 4-1BB-based CAR-T cells have a similar 12-months OS rate and 3-months CRR with CD28-based products but a better safety profile. The costimulatory domain might not affect the survival outcomes.